Multicriteria optimization in telecommunication networks planning, designing and controlling - Bezruk, V. M.; Bukhanko, O. M. (ХНУРЭ, 2011)
Some features of methodology of telecommunication networks optimal design variants choice taking into account of the quality indicators are represented. In the presented work multycriteria optimization methods application in planning of cellular networks, optimal routing, choice of speech codec, controlling network resources are given too.
Keywords: telecommunication networks